Hyperbranched poly(amidoamine)/TMC reverse osmosis membrane for oily saline water treatment. Issue 21 (19th September 2019) - Pei, Biao; Chen, Junjie; Liu, Peng; He, Tao; Li, Xuemei; Zhang, Lin
ABSTRACT: Generally, conventional polyamide reverse osmosis (RO) membranes suffer from a low water flux and serious oil pollution in the treatment of oil saline wastewater. Here, a novel RO membrane was successfully fabricated with hyperbranched polyamidoamine (PAMAM) and trimesoyl chloride (TMC) by interfacial reaction on polysulfone ultrafiltration membrane surface. The relatively smooth and thin PAMAM and TMC crosslinking active layer on the substrate membrane endowed the composite membrane with an excellent separation performance and remarkable anti-fouling performance simultaneously. For the stable saline emulsion with an oil droplet size of 300 nm, the rejection of oil and NaCl reached to 99% and 89.3% respectively, and the water flux was about 18.42 L/(m 2 h). After 24-h continuous operation, the rejection of oil and salt maintained above 98% and 88%, and the flux only decreased about 5%, exhibiting a more excellent resistance to oil pollution than the commercial membrane, of which the flux sharply decreased by 30%. Hence, it is believed that such membrane has great potential for effective separation of oily saline wastewater.